2011
DOI: 10.1016/j.jmii.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester suppresses eotaxin secretion and nuclear p-STAT6 in human lung fibroblast cells

Abstract: CAPE inhibited the production of eotaxin protein in stimulated human lung fibroblast cells in a dose-dependent manner. This activity is, at least, through STAT6 inhibition. We suggest that CAPE is a promising agent in controlling eotaxin secretion and subsequent eosinophils influx and may therefore have a potential role to play in treating allergic airway disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The suppressive capacities of these 13 compounds on the secretion of RANTES, eotaxin and eotaxin-3 were evaluated in BEAS-2B cells. The BEAS-2B cell line was induced using TNF-α or TNF-α in combination with IL-4, as it was reported that their combination may enhance the production of eotaxin in human lung fibroblasts, airway epithelial cells, smooth muscle cells and dermal fibroblasts (28).…”
Section: Discussionmentioning
confidence: 99%
“…The suppressive capacities of these 13 compounds on the secretion of RANTES, eotaxin and eotaxin-3 were evaluated in BEAS-2B cells. The BEAS-2B cell line was induced using TNF-α or TNF-α in combination with IL-4, as it was reported that their combination may enhance the production of eotaxin in human lung fibroblasts, airway epithelial cells, smooth muscle cells and dermal fibroblasts (28).…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid phenethyl ester (CAPE) is derived from different plants and is a bioactive constituent found in bee propolis that may have pharmacological applications. Recently, a wide range of pharmacological properties were demonstrated for this substance, including antiinflammatory, antioxidant, antiproliferative, and immunomodulatory activities (6)(7)(8). The prominent protective property of CAPE makes it a potential therapeutic compound against damage to the kidneys, brain, lungs, and other tissues or organs.…”
Section: Introductionmentioning
confidence: 99%